EFFECTS OF INTERPHASE AND MATRIX PROPERTIES ON EFFECTIVE TENSILE ELASTIC MODULUS OF CARBON NANOTUBE-BASED COMPOSITE - Masud, AKM; Tahreen, Nabila; Abedin, Farhana (Journal of Mechanical Engineering, 2009)
The aim of this research is to assess the effects of interphase property and matrix property on the tensile elastic modulus (TEM) of the carbon nanotube (CNT) using a 3-D nanoscale representative volume element (RVE) based on continuum mechanics and using the finite element method (FEM). Formulas to extract the effective material constants from solutions for the RVE is derived based on the elasticity theory. Based on the strength of materials theory, an extended rule of mixtures, for estimating the effective Young's modulus, is applied for comparisons with the numerical solutions based on the elasticity theory. Both long and short CNT embedded in matrix at a volume fraction of 2% and 5% respectively is considered for investigating the effects of interphase and matrix property variation. The results demonstrate that in both the cases, matrix property and interphase property significantly influence the TEM of the CNT based composite. These results suggest that a coating of harder polymer on the CNT or a surface treatment can significantly increase the TEM of CNT based composite. Keywords: Carbon nanotube, Nanocomposites, Interphase, Tensile elastic modulus, FEM. doi: 10.3329/jme.v40i1.3471 Journal of Mechanical Engineering, Vol. ME40, No. 1, June 2009 29-38